IDDF2020-ABS-0158 BRAF mutation induces rapid neoplastic transformation in the aged and extensively hypermethylated intestinal epithelium. (18th November 2020) - Fennell, Lochlan; Kane, Alexandra; Liu, Cheng; McKeone, Diane; Hartel, Gunter; Bond, Catherine; Bettington, Mark; Leggett, Barbara; Whitehall, Vicki
Abstract : Background: Sessile serrated lesions (SSL) are common in both young and old individuals, but the BRAF mutant cancers arising occur predominantly the elderly. DNA Methylation is uncommon in SSL from young patients. Here we interrogate the role of aging and DNA methylation in SSL initiation and progression. Methods: We used an inducible model of Braf mutation to direct recombination of the oncogenic Braf V637E allele to the murine intestine. BRAF mutation was activated after periods of aging, and histological and DNA methylation analysis was performed thereafter. We investigated DNA methylation alterations in human SSLs. Results: Inducing Braf mutation in aged mice was associated with a 10-fold relative risk of serrated lesions compared with young mice. Methylation analysis revealed extensive differences in age-associated DNA methylation between animals induced at 9 months versus wean; with relatively little differential Braf-specific methylation, implicating age-associated DNA methylation rather than Braf-specific DNA methylation in the heightened risk. DNA methylation at WNT pathway genes scales with age and Braf mutation accelerated age-associated DNA methylation. In human SSLs, increased epigenetic age was associated with high-risk serrated colorectal neoplasia. Conclusions: SSLs arising in the aged intestine are at a significantly higher risk of spontaneous neoplastic progression. These findings support a new conceptual model for serrated neoplasia whereby the risk of progression is related to the milieu of epigenetic alterations in the intestinal epithelium at the time of BRAF mutation, rather than the length of time since polyp initiation. This has implications for surveillance and chemopreventive strategies targeting the epigenome.